2011
DOI: 10.1007/s12022-011-9166-7
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Sarcoma of the Sellar Region

Abstract: Malignancies lacking specific features of cellular maturation are termed "undifferentiated" and represent 5-10% of all human tumors. They are encountered at a variety of sites but do not, as a rule, arise in the sellar region. A 39-year-old male with a history of testicular seminoma and an unsuccessful biopsy of a third ventricular neoplasm, presented with visual disturbances and memory loss. Light microscopically, the tumor consisted entirely of undifferentiated spindle cells. No germ cell component was noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…To the best of our knowledge, our case represents the second reporting of a sellar undifferentiated spindle cell sarcoma. Interestingly, in the previous report of undifferentiated sellar spindle cell sarcoma, a consideration was that the tumour in some way may have been related to the patient’s previous testicular seminoma, either as a metastasis or as a separate de novo lesion 16. Our case represented a true form of primary intrasellar undifferentiated tumour, as the patient had no history of malignancy and his PET scan did not show any evidence of other tumours.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…To the best of our knowledge, our case represents the second reporting of a sellar undifferentiated spindle cell sarcoma. Interestingly, in the previous report of undifferentiated sellar spindle cell sarcoma, a consideration was that the tumour in some way may have been related to the patient’s previous testicular seminoma, either as a metastasis or as a separate de novo lesion 16. Our case represented a true form of primary intrasellar undifferentiated tumour, as the patient had no history of malignancy and his PET scan did not show any evidence of other tumours.…”
Section: Discussionmentioning
confidence: 69%
“…Our extensive review of the Pubmed and Medline literatures have revealed only three case reports to date of primary intrasellar spindle cell sarcomas without prior radiation exposure 2 15 16. Two of these reports identified the primary sellar tumour as fibrosarcoma,2 15 and one report was of an undifferentiated sarcoma 16. That one case represented the first sellar example of an undifferentiated spindle cell sarcoma in medical literature, which showed desmin reactivity alone, without other immunohistochemical or ultrastructural features of rhabdomyosarcoma 16.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations